IMPLEMENTASI MEDIA PEMBELAJARAN INTERNET OF THINGS (IOT) UNTUK SISTEM KENDALI LAMPU OTOMATIS BAGI SISWA SMKN 1 BANYUANYAR PROBOLINGGO - Amalia Herlina; M. Fikri Syarif Ramdhoni; Moh. Syaifullah (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
This PKM activity was carried out based on a situation analysis to explore the main problems faced by partners, namely the low insight and ability of students to understand IoT and its implementation for automatic control systems. The reason is because this material is not given in a special subject, but is part of the Electronics Engineering course. Another cause is the impact of online learning which is not optimal during the PPKM Covid 19 period, especially for the implementation of practicum. PKM was carried out by the PKM Team from the Department of Electrical Engineering, UNUJA Paiton, aimed at 35 students of SMKN 1 Banyuanyar, Department of Industrial Electrical Engineering, 11th grade. The team created an IoT learning module for the Automated Light Control System consisting of Teaching Aids, Learning Modules and Videos containing introductory materials and introduction to IoT (simple learning). This is in accordance with the conditions of students who need basic level of IoT knowledge, because they have never had this knowledge before. The implementation of this PKM can run smoothly and obtain results in accordance with the objectives. The results of the program evaluation show that the 6 achievement indicators have been well achieved. In the implementation of the before after test, there was an increase of 92% in the post-test. As a follow-up to this PKM, it is recommended that schools develop existing learning modules so that technology adaptation can continue to be carried out and is beneficial for increasing knowledge and understanding of IoT for both students and teachers